American Adventures : Elementary Student Book and Workbook A - Wetz, Ben and Gammidge, Mick (Karachi, Pakistan Oxford University Press, 2008)
A four-level course with international topics and cultural themes, providing extra motivation for students.
Include Illustration
Keywords: United States -- English language -- English language--Study and teaching--Foreign speakers